Development of flood inundation maps as an initial assessment for flood disaster mitigation - a case study of selagan river basin. Issue 1 (April 2021) - Fernando, R; Utama, A B; Taurano, G A; Riani, L; Moe, I R
Abstract: Flood is a natural disaster that often occurs in Bengkulu Province. One of which occurred at the Selagan River Basin which caused in several sub-districts in Mukomuko District to be flooded. Goverment must be fast and precise in resolving future flooding problems in the Selagan River Basin. In solving the problem, initial assessment data is certainly needed, one of which is a flood inundation map, so that later the infrastructure that is built is right to solve the flooding problem that occurred in the Selagan River basin. This study was conducted to model section of the Selagan River for flood inundation forecasting with the help of digital elevation model (DEM) Data, hydrological data, river characteristics data, geographical information system(GIS). Those data is used to create a flood inundation model that is built with hydrodynamic modules which consist of rainfall runoff module, flood routing and inland flooding by using the MIKE software. Simulations of flood inundation that has been made are compared using inundation observation data at flood locations, so the results of flood inundation maps occur at this time can be a preliminary assessment for flood mitigation in the future.